The forward problem of magnetometry for the oblate spheroid - Milan HVOŽDARA (Contributions to Geophysics and Geodesy, 2011)
We present analytical solution of the forward magnetometric problem for the oblate spheroid (rotational ellipsoid) as a causative body. The shorter semiaxis of the ellipsoid is supposed to be vertical to the surface of the earth. There is proved that the uniform inducing magnetic field B0 induces inside the spheroid also uniform magnetic field but its modulus and direction are different as compared to B0. The isolines and profile curves of ΔZ and ΔT are calculated on the plane z = const above the ellipsoid, as well as on the surface of the hill in the shape of cutted cone.